Geophysical evidence for breakup volcanism in the Angola and Gabon passive margins. (June 2020) - Fernandez, O.; Olaiz, A.; Cascone, L.; Hernandez, P.; Pereira, A. de F.; Tritlla, J.; Ingles, M.; Aida, B.; Pinto, I.; Rocca, R.; Sanders, C.; Herrá, A.; et al.
Abstract: Serial two-dimensional reflection seismic profiles spanning the continent-ocean transition in the offshore Kwanza and southern Gabon basins have been interpreted and integrated with 2.5D gravity and magnetic anomaly modelling. These continental margins are characterized by the presence of a distal domain in which continental crust has been highly stretched and faulted, overlain by thick sequences of Early Cretaceous syn-rift sediments, that are in turn overlain by a thick but highly deformed Aptian evaporite unit. The evaporites are overlain by post-breakup sediments (Cretaceous to Recent in age). Oceanwards, syn-rift sediments are overlain by a volcanic unit that thickens basinward. This volcanic unit forms the base and the lateral-equivalent of the distal evaporite basin, developing into positive-relief volcanic edifices that acted as the oceanward margin of the evaporite basin. These volcanic units extend from the distal domain of the passive margin to the oceanic crust and are interpreted to represent volcanism that immediately predates lithospheric breakup and formation of oceanic crust, as indicated by the progressive transition into a constant-thickness oceanic crust. Volcanism synchronous with the late stages of passive margin development, and related hydrothermalism, can account for the high alkalinity that dominated the pre-salt lacustrine environments and could also have contributed to the modification of marine waters that led to the deposition of the thick Aptian evaporites in the South Atlantic Ocean. Breakup volcanism and its associated thermal impact can also help explain the apparently anomalous shallow water depth of these margins preserved during the latest rift and earliest post-rift stages. Graphical abstract: Image 1 Highlights: Distal Gabon and Angola passive margin structure defined from geophysical data. Presence of breakup volcanism documented along both margins. Breakup volcanism predates and is synchronous to the Aptian evaporites.